Core Competencies in Small Manufacturing Firms a Case Study - Md. Mostaque Hussain; Mawdudur Rahman; Muhammed Nurul Alam (Journal of Accounting, Business and Management (JABM), 2006)
A number of researchers have claimed that core competencies are very important factors in the success of the company. According to them, companies should identify their core competencies and use the knowledge to manage the company. In this case study the firm has been viewed from resource-based theory point of view, which builds on assumptions that firms are different because they have different resources. Core competencies can be seen as one of the resources of the firm. This study tries to identify core competencies of a small manufacturing company and find out whether and how competencies can successfully be used in managing a small company